2014
DOI: 10.1021/nl501239h
|View full text |Cite
|
Sign up to set email alerts
|

Record Pure Zincblende Phase in GaAs Nanowires down to 5 nm in Radius

Abstract: We report the Au catalyst-assisted synthesis of 20 μm long GaAs nanowires by the vapor-liquid-solid hydride vapor phase epitaxy (HVPE) exhibiting a polytypism-free zincblende phase for record radii lower than 15 nm down to 5 nm. HVPE makes use of GaCl gaseous growth precursors at high mass input of which fast dechlorination at the usual process temperature of 715 °C results in high planar growth rate (standard 30-40 μm/h). When it comes to the vapor-liquid-solid growth of nanowires, fast solidification at a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
130
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 52 publications
(104 reference statements)
4
130
2
Order By: Relevance
“…the well-known results used extensively in modeling of NW growth 12,14,20,21,34 . Very importantly, the surface energy constant a is determined by the ratio of the characteristic surface energy per …”
Section: Nucleation Rate Of Iii-v Islands Growing From a Ternary Liquidmentioning
confidence: 99%
See 2 more Smart Citations
“…the well-known results used extensively in modeling of NW growth 12,14,20,21,34 . Very importantly, the surface energy constant a is determined by the ratio of the characteristic surface energy per …”
Section: Nucleation Rate Of Iii-v Islands Growing From a Ternary Liquidmentioning
confidence: 99%
“…In the case of semiconductor nanowires (NWs) fabricated by the metalcatalyzed vapor-liquid-solid (VLS) method 10 , the ZNR is thought to determine the probability of 2D nucleation from a supersaturated liquid alloy of a metal catalyst with the growth constituencies 2 . In this way, the ZNR controls the vertical growth rate of NWs 2,11-13 , nucleation statistics in VLS NWs [14][15][16][17] , morphology of the growth interface 18,19 and even the preferred crystal structure of Au-catalyzed III-V NWs which can be either cubic zincblende (ZB) or hexagonal wurtzite (WZ) [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] . Since most NWs grow in the so-called mononuclear mode with only one island emerging in each NW monolayer (ML) 2 , we need to consider the chain of individual nucleation events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the growth direction [38] or the crystal structure [34,36,37] However, the understanding of the mechanism behind these parameters are very limited. Very recently, Gil et al [35] reported the growth of pure ZB phase GaAs NWs with diameter between 5 and 15 nm, as shown in Fig. 3a.…”
Section: Section Ii: Crystal Structure and Morphology Of Iii-v Nanowimentioning
confidence: 97%
“…2). For a long time, experimentalists have shown that by changing the growth parameters, such as NW diameter [34,35], growth temperature [36], or precursor flow [37] employed during the growth, it is possible to modify the stacking order of the bilayers. Consequently, the growth direction [38] or the crystal structure [34,36,37] However, the understanding of the mechanism behind these parameters are very limited.…”
Section: Section Ii: Crystal Structure and Morphology Of Iii-v Nanowimentioning
confidence: 99%